Making Sense of Data: Objectivity and Subjectivity, Fact and Value - Paul Standish (Charles University, 2017)
ABSTRACT Data can seem to be the very foundation of research, the sine qua non of enquiry into education. Yet this thought can be troubled by questions about the provenance of data or about how something comes to be constructed as data in the first place. And most researchers face questions about what to do with data when it arrives - where, in the social sciences more than the physical sciences, results of tests rarely show conclusively what to do next, and where, in light of this, interpretation comes to the fore. The present discussion explores problems of objectivity and subjectivity, and of fact and value, as these arise in relation to these matters. The idea that the mind is more or less separate from the body and the idea that there is a realm of fact distinct from the realm of value in many respects laid the way for contemporary notions of objectivity and subjectivity, not least in the social sciences. Yet both are now widely discredited. The present discussion will illustrate the nature of the reappraisal that, in consequence, is needed. The argument that unfolds will help to reveal the need for a reorientation of education - in research, policy, and practice - such that the role and importance of the exercise of judgement is better understood. There are implications here for research methods training and for the funding that facilitates responsible enquiry into education.